2013
DOI: 10.1002/cbf.2983
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid in the treatment of post‐diabetes testicular damage: relevance to the down regulation of apoptosis correlates with antioxidant status via modulation of TGF‐β1, IL‐1β and Akt signalling

Abstract: The aim of this study was to investigate the protective effect of ferulic acid at different doses (50 mg kg(-1) alternative day and 50 mg kg(-1) daily) on the streptozotocin (STZ)-induced post-diabetes rat testicular damage. Diabetes was induced by a single intraperitoneal injection of STZ (50 mg/kg). Rats treated with ferulic acid were given once a day orally for 10 weeks, starting 3 days after STZ injection. Testis tissue and blood samples were collected for investigating biochemical analysis, antioxidant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 44 publications
1
29
0
1
Order By: Relevance
“…31 TGF-β1 is observed in the round spermatids and Leydig cells of matured mouse testes over 50 days of age. 33 In the current study, HS significantly increased the gene expression of TGF-β1 in the testes, but curcumin significantly reduced the mRNA level of TGF-β1 overexpressed by HS. 33 In the current study, HS significantly increased the gene expression of TGF-β1 in the testes, but curcumin significantly reduced the mRNA level of TGF-β1 overexpressed by HS.…”
Section: Discussionmentioning
confidence: 40%
“…31 TGF-β1 is observed in the round spermatids and Leydig cells of matured mouse testes over 50 days of age. 33 In the current study, HS significantly increased the gene expression of TGF-β1 in the testes, but curcumin significantly reduced the mRNA level of TGF-β1 overexpressed by HS. 33 In the current study, HS significantly increased the gene expression of TGF-β1 in the testes, but curcumin significantly reduced the mRNA level of TGF-β1 overexpressed by HS.…”
Section: Discussionmentioning
confidence: 40%
“…Blood metabolite concentrations were within reference ranges (Kaneko et al, 2008), suggesting that ewes used had an adequate health status. In fact, in diabetic rats with high oxidative stress, Yoo et al (2012) and Roy et al (2014) reported that FA supplementation improved oxidative status while blood glucose and insulin concentrations returned to normal levels. This situation can lead to health problems in sheep and also provoke metabolic changes that reflect in imbalances of blood metabolite levels (Drackley, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the FA is covalently linked to lignin and polysaccharides by ester and ether bonds, and thereby provides rigidity, strength, and protection from attack of microorganisms to plants (Kroon and Williamson, 1999). Furthermore, in its free form, FA is characterized as a bioactive compound that provides antioxidant properties for animals (Gladine et al, 2007;Roy et al, 2014) and humans (Manach et al, 2004;Ou and Kwok, 2004), and recent studies reported that also acts as a growth promoter in beef cattle (González-Ríos et al, 2013) and pigs (Herrera et al, 2011). In fact, compared with other natural antioxidant, this metabolite has proved be more effective to prevent lipid and protein oxidation (Rose et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent effects of DM on the male reproductive system include decreased levels of testosterone, lower testicular weight, abnormal spermatogenesis, alterations in sperm count and motility, and histopathological changes in testis tissue components [2][3][4][5] . Abnormalities in spermatogenesis due to increased apoptosis have been demonstrated in certain studies 2,3,[6][7][8][9][10] . Testicular apoptosis may be the major component of the infertility.…”
Section: Introductionmentioning
confidence: 99%